2019
DOI: 10.3390/jcm8070952
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Efficacy of PRRT in Patients with Advanced, Nonresectable, Paraganglioma-Pheochromocytoma, Related to SDHx Gene Mutation

Abstract: Paragangliomas and pheochromytomas (PPGLs) exhibit variable malignancy, advanced/hormonally active/progressive need therapy. PRRT (Peptide Receptor Radionuclide Therapy) could be an option for these patients. To evaluate the effectiveness of PRRT (90Y DOTATATE), based on overall survival (OS) and progression-free survival (PFS), in patients with PPGLs, related to SDHx gene mutation, we conducted a prospective open-label, single-center, phase II study. Thirteen patients were observed, eight PGL1 and five PGL4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…A diagnostic approach with 68Ga Dota-peptide PET/CT 10 and the therapeutic use of 90Y-DOTATOC and 177Lu-DOTATATE 11 , 12 , 13 in GEP-NETs has paved the way for their use in other NET histologies, including paragangliomas. 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…A diagnostic approach with 68Ga Dota-peptide PET/CT 10 and the therapeutic use of 90Y-DOTATOC and 177Lu-DOTATATE 11 , 12 , 13 in GEP-NETs has paved the way for their use in other NET histologies, including paragangliomas. 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Other centers have reported, 24 h following 177-LUDOTATE infusion, severe tumoral lysis syndrome which led to severe hypertension, shortness of breath, tachycardia, hyperkalemia, hyperphosphatemia and hypocalcemia with necessary admission to ICU [ 22 ]. Other patients developed severe hypotension or severe tachycardia during treatment infusion [ 16 , 17 , 21 , 22 , 25 , 26 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scientific community appears to be sensitized to the fact that pharmacological treatment of pheochromocytoma and functional paraganglioma before surgery is of vital importance in these patients. However, several authors agree that metastatic functional paraganglioma and pheochromocytoma, which are candidates for PRRT, need to be pretreated and certain protocols should be assessed during treatment infusion in order to avoid the hormonal crisis previously described [ 16 , 17 , 21 , 25 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study from 2019 by Kolasinska-Cwikla et al, 13 patients with metastatic SDHB and SDHD (n=5 and 8, respectively) were treated with 90 Y-DOTATATE, with an 82% response of stable disease after 1 year. The median OS and PFS were 68 months and 35 months, respectively, with no difference in the endpoints in patients who were either secretory or nonsecretory (94). A retrospective study assessing 90 Y-DOTATATE and 131 I-MIBG concluded that mPGLs were best suited for treatment by SSA-based PRRT.…”
Section: Y-based-ssa Prrtmentioning
confidence: 99%